O processo de aquisição da leitura na escola: as contribuições da literatura infantil - santana, Maria Rosinélia Dias de (2015)
Our aim in this research study the process of reading acquisition, whereas the contributions of Children's Literature in Brazil. As an object of study, we chose the tale of Children's Literature to understand that such textual genre enchants, and experience the events of daily life of students as readers beginners, whose age range between 06 to 07 years, the Municipal School - Annex Rural Base, Olinda-PE. As the theoretical, are talking with authors who work with the process of reading with the textual genres of Children's literature, as Abramovich (1997), Coelho (2000), Lajolo (1982, 1984, 2002), Sole (1998), Zilberman (1985, 1987, 1990); in relation to the theory of Children's literature, with Cademartori (1986), Frantz (2001), among others. As for the methodology, it is an exploratory research, literature review of qualitative nature. In relation to the collection of data, were collected from activities implemented in a sequence didactics, with students from the 1ST Year of the Elementary School, which was considered readers beginners at an age between 06 and 07 years old. And for analysis of the data, we take the understanding of content analysis from the perspective of Bardin (2011) in order to obtain the results achieved in the course of the sequence didactics. Through the application, as a proposal for intervention, to analyze the data we can see that the strategies of reading, taking the feature tales of Children's Literature provides the reader an enhancement of their creativity, it stimulates the imagination, the intellect, the emotions among other feelings that in the future this will become a critical player, able to exercise their rights of citizenship, aware of the social reality in which it is inserted and the possibilities to transform it. The research points out that Children's Literature contributes to the process of the acquisition of reading, the awakening, the child, the curiosity and the need to be a player, ensuring conditions for it represents the world and life through words.